Qualitative Analysis of the SNS Role in Information Avoidance from the Perspective of S-O-R (Stimulus-Organism-Response) Theory - Kumalasari, Rahmania; Priharsari, Diah; Aknuranda, Ismiarta (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
Today, many people and organizations use SNS to disseminate information regarding COVID-19. However, information avoidance can still occur if users refuse to receive the information. Although previous research on information avoidance has been conducted, this research brings novelty by showing that the SNS design leads to information avoidance from the opinion and human behavior perspective. Therefore, this study analyzed the role of SNS in information avoidance from the perspective of SOR theory qualitatively. This research was conducted in Indonesia, which has the most significant SNS users on subjects who feel the impact of information overload and anxiety. It aimed to comprehend the phenomenon's effect on SNS users and the factors driving information avoidance. This research provided two contributions from the thematic analysis process. The first was to show the conceptual model of information avoidance related to the factors driving information avoidance and information anxiety from the perspective of SOR theory. The second was to provide knowledge about the impact of SNS on user behavior.